Implementation of the Safe Reduction of Primary Cesarean Births Safety Bundle During the First Year of a Statewide Collaborative in Maryland. Issue 1 (July 2019) - Callaghan-Koru, Jennifer A.; Creanga, Andreea A.; DiPietro, Bonnie; Mark, Katrina; Sowe, Ardy; Aboumatar, Nour; Burke, Ann B.; Curran, Geoffrey
Abstract : OBJECTIVE: To describe the status of implementation of the Alliance for Innovation in Maternal Health's primary cesarean birth patient safety bundle in Maryland after 1 year (2016–2017), and assess whether hospital characteristics and implementation strategies employed are associated with bundle implementation. METHODS: The Alliance for Innovation in Maternal Health's bundle to decrease primary cesarean births includes 26 evidence-based practices that hospitals can adopt based on specific needs. One year after the start of a statewide implementation collaborative at 31 of 32 birthing hospitals in Maryland, we sent a computer-based survey to hospital collaborative leaders to assess progress. Respondents reported on hospital characteristics, adoption of bundle practices, and use of 15 selected implementation strategies. We conducted descriptive and bivariate analyses of their responses. RESULTS: Among 26 hospitals with complete reporting, 23 fully implemented at least one bundle practice (range 1–7) during the collaborative's first year. Of 26 bundle practices, on average, hospitals had fully implemented a third (mean 8.6; SD 5.5; range 0–17) before the collaborative, and 3 new practices (SD 2.4; range 0–8) during the collaborative. Hospitals' use of six implementation strategies, all highly dependent on strong clinician involvement, was significantly associated with their fully implementing more practices during the collaborative's first year. CONCLUSION: Our assessment has promising results, with a majority of hospitals having implemented new cesarean birth bundle practices during the collaborative's first year. However, there are lessons from the wide variability in the number and type of practices adopted. Clinicians should be aware of this variability and become more involved in the implementation of cesarean birth bundle practices. We identified six strategies associated with full implementation of more bundle practices for which clinicians' support and commitment to practice changes are critical. Clinicians' understanding of available and effective implementation strategies can better assist with the implementation of this and other Alliance for Innovation in Maternal Health patient safety bundles. Abstract : Hospitals adopted an average of three new cesarean birth bundle practices during the collaborative's first year; six implementation strategies were associated with greater practice adoption.